Fulfillment of The Rights of Accessibility to Population and Civil Registration for People with Disabilities - Asriyani Asriyani; Adiesty Septhiany P. Syamsuddin; Abd. Halik (Universitas Batanghari Jambi, 2023)
The objective of this study is to discover the legal position of the National ID number functioning as the primary identity that forms the basis for fulfilling citizens’ rights, including fundamental rights to health services and education for persons with disabilities. Also, to determine the innovation implemented by the Dinas Adminduk of Palu City to encourage public service fulfillment for persons with disabilities. This research is empirical legal research with statutory and conceptual approaches. This research concludes that the legal position of the National ID number functioning as the primary identity that forms the basis for fulfilling citizens’ rights has been legalized in the Regulation of The President of The Republic of Indonesia Number 83 Year 2021. This causes every Indonesian citizen to be mandatory to have an ID number to access public services, which leads to the fulfillment of the constitutional rights of citizens. SIMALEO BERGERAK, PELANGI in the District, and PELAYAN SEKSI are the innovations developed to help the citizens, especially persons with disabilities, to have an ID number. Therefore, the obligation to fulfill the constitutional rights of persons with disabilities can be carried out by the State.